Design player robot badminton-based microcontroller - Rachmadiaz Miranto; Jajang Jaenudin; Mustaza Ma’a; Luqman Hakim (Teknik Mesin - Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2024)
Robots are one of the technologies that is currently advancing quickly. Generally speaking, a robot's movement is similar to that of an automobile; it can only move forward, backward, left, and right. Because the movement is controlled by these movements, it is thought that the robot's movement is extremely restricted to the left and right directions. solely with the front wheels. As a result, a robot was developed in this study that can control sliding motions to the left and right utilizing omniwheels on its front and back wheels. Badminton is a sport involving rackets that is played by two people or two opposing pairs. Robotic badminton players are employed as a substitute for human trainers in the training process, particularly for service and drive motions. With the use of a wireless joystick, the robot's ATMega 8535 microprocessor controls both the robot's direction of motion and the movement of its racket. Using a double acting pneumatic cylinder that requires 7 bar of air pressure, the robot service arm uses the compressor's air pressure. The average time it takes for the racket to strike the ball at 7 bar of wind pressure is 00:5.2 seconds. The time it takes for the ball to fall onto the racket in the absence of wind pressure is 00:28 seconds on average. A difference value of 00:22.7 seconds is acquired, and this value will be utilized as the programming reference delay. The robot encounters a slope with an average angle change of 7º when moving forward, an average angle change of 10º when moving backward, an average angle change of 5.2º when moving right, and an average angle change of 3º when moving left. The uneven field surface causes the robot to move at a slope, which modifies the speed of the motor on the wheels